Union Bargaining Power and the Amenity-Wage Tradeoff - Lorenzo Lagos (Institute of Labor Economics (IZA), 2024)
This paper studies the relation between the wage and amenity components of compensation under collective bargaining. Using the universe of collective bargaining agreements (CBAs) in Brazil, I augment information on workers' wages with the comprehensive set of amenities codified in the text of these contracts. I then estimate the effects of increasing union bargaining power with a difference-in-difference strategy that leverages 1) a judicial decision that prevented the expiration of existing CBA provisions—a policy known as ultractivity—and 2) gaps in CBA coverage across establishments when the policy was enacted. I find that boosting union power causes an increase in both wages and CBA clauses without a subsequent decrease in employment. A revealed preference approach to estimating the wage-equivalent value of negotiated clauses shows that amenity value also increases, comprising approximately 45% of workers' total gains in compensation. Results are consistent with collective bargaining functioning as a labor market institution that counters monopsony power, but where employers retain the right-to-manage the composition of their workforce.
Keywords: J52; J32; J42; K31; 330; collective bargaining; unions; amenities; compensating differentials